Norwegian Gross Domestic Product by Industry 1830 - 1930 - Ola Honningdal Grytten (Norges Bank, 2015)
The present paper offers new knowledge of historical national accounting in Norway in several ways. Firstly, a new and novel set of annual gross domestic product series by industry are presented for the period 1830-1930. Secondly, the new estimates suggest revision of the historical national accounts published by Statistics Norway. Thirdly, this may lead to necessary revisions of both Norwegian industrial history and business cycle history.
hdl:11250/2495805
Keywords: L6; L7; L8; L9; N3; N13; N14; O11; O14; O16; 330; Norwegian economic history; historical national accounting; industrial development; national accounts